IMPLEMENTASI STANDAR OPERASIONAL PROSEDUR DALAM PELAYANAN BPJS KESEHATAN DI RSU PROF. DR. KANDOU MANADO - Pinontoan, Monalisa Eirene; Dengo, Salmin; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : In early 2014 the government held health insurance for all of society,namely the National Health Insurance with the program implementing agency is the Agency Social Security Health.Institution of Social Security health,is a helath insurance program for all people.In the program of social security health agencies have determined a standard operating procedure for a smooth service to be provided.In connection with this research was to determine how to implementation of standard operating procedures in the ministry of health of social security agencies in public hospitals Prof.Dr.Kandou. This study used a qualitative research method using four variables from the policy implementation Edward George III consisting of communication, resources, disposition and bureaucratic structure through interviews to 15 informants.Observation and document tracking aided additional instruments such as interview guides. Based on the results of the study show that the first variable communications program managers,service providers and the community is effective,human resources and adequate financial resources also,the third variable that is the dispositionof executing and caregiversviews of commitment and consistency is good enough,and the last variable that the existing bureaucratic structure has been arranged in accordance with the provisions in force. Based on the results obtained it can concluded that the implementation of standard operating procedure in the ministry of social security organizing body public healthhospital Prof.Dr.Kandou pretty well and runs fairly effectively viewed from four variables implementation of Edward III.Suggested should be increased again in the effectiveness and efficiency of exsting standard operating procedures in the ministry of social security agencies in order to become better health and quality. Keyword :Implementation, Standard Operating Procedures